(untitled) (Medical Forum Monthly, 2024)
Study Design: Experimental study. Place and Duration of Study: This study was conducted at various hospitals of Quetta. Materials and Methods: This study includes 103 cases of chronic granulomatous lymphadenitis, with 101 cases of tuberculosis lymph nodes amongst a total of 200 cases of non-neoplastic lymphadenopathy.Their ages ranged from 2 to 79 years. Maximum number of cases were in 10-29 years age group. Females (69.31%) were affected more as compared to males. The commonest presenting symptom was fever. Cervical lymph nodes (83 cases) were the commonest site of involvement whereas 18 cases showed multiple site involvement. Fluorescent staining of histopatholigical sections from 103 chronic granulomatous lymphadenitis gave positive results in 76 out of 103 (73.78%) cases, however Ziehl-Neelsen staining was positive only in 29 out of 103 (28.15%) cases. The yield of mycobacteria on fluorescent staining was higly significant (p<0.001) as compared to ZiehlNeelsen staining thereby providing the superiority of fluorescent stain. Result: In a total of 200 cases of non-neoplastic lymphadenopathy 101 cases showed granulomatous lesions, histologically consistant with tuberculosis. Other causes of lymphadnopathy were chronic non-specific lymphadenitis (n=87) viral lymphadenitis (n=8), fungal lymphadenitis (n=2) and acute bacterial lymphadenitis (n=2). Fluorescent staining of histopathological sections from 103 chronic granulomatous lymphadenitis gave positive results in 76 out of 103 (73.78%) cases, however Ziehl-Neelsen staining was positive only in 29 out of 103 (28.15%) cases. In 101 cases, the finding were consistent with the diagnosis of tuberculous lymphadenopathy. In our study, significantly greater number of cases, 78 out of 101 (P<0.001) diagnosed as tuberculous lymphadenitis were in age groups 10-29 years. Female (69.31%) were more affected than males (30.69%). The common presenting symptom was fever. Cervical lymph nodes were commonest site of biopsy. Haemoglobin estimation in 98 cases revealed anaemia in 65 out of 101 (66.32%) patients of tuberculous lymphadenopathy. Erythrocyte sedimentation rate was performed in 63 cases and was raised in 52 (82.53%) cases. In a total of 80 cases in whom X-ray chest was performed, 14 (15.5%) cases revealed foci of tuberculosis. Conclusion: Thus, in conclusion, this study has highlighted the superiorty of fluorescent stain over ZN stain.